2021
DOI: 10.1002/cjp2.241
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the tumor microenvironment in rare renal cancer histological types

Abstract: The tumor microenvironment (TME), including immune cells, cancer-associated fibroblasts, endothelial cells, adjacent normal cells, and others, plays a crucial role in influencing tumor behavior and progression. Here, we characterized the TME in 83 primary renal tumors and matched metastatic or recurrence tissue samples (n = 15) from papillary renal cell carcinoma (pRCC) types 1 (n = 20) and 2 (n = 49), collecting duct carcinomas (CDC; n = 14), and high-grade urothelial carcinomas (HGUC; n = 5). We investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
0
10
1
Order By: Relevance
“…Clinical treatment with immune checkpoint inhibitors in combination with anti-angiogenic therapies has demonstrated positive effects on the clinical outcomes for patients with ccRCC, suggesting that the TME facilitates renal cancer development [ 182 ]. The TME of more aggressive renal cancers, like papillary RCC (pRCC) and collecting duct carcinomas, was also analyzed and found to have different marker expression for immune infiltration, vasculature, cell proliferation, and epithelial-to-mesenchymal (EMT) transition [ 183 ]. Therefore, the influence of TME in renal cancer should be more seriously considered in clinical treatment and better investigated to promote personalized therapies (See Table 3 ).…”
Section: Bioprinting To Mimic the Urological Tmementioning
confidence: 99%
“…Clinical treatment with immune checkpoint inhibitors in combination with anti-angiogenic therapies has demonstrated positive effects on the clinical outcomes for patients with ccRCC, suggesting that the TME facilitates renal cancer development [ 182 ]. The TME of more aggressive renal cancers, like papillary RCC (pRCC) and collecting duct carcinomas, was also analyzed and found to have different marker expression for immune infiltration, vasculature, cell proliferation, and epithelial-to-mesenchymal (EMT) transition [ 183 ]. Therefore, the influence of TME in renal cancer should be more seriously considered in clinical treatment and better investigated to promote personalized therapies (See Table 3 ).…”
Section: Bioprinting To Mimic the Urological Tmementioning
confidence: 99%
“…Recent research has found that the complex heterogeneity of the renal tumor was reflected in the composition of the TME. The tumor core of papillary renal cell carcinoma was mainly enriched with macrophages, while the periphery of collecting duct carcinoma was mostly rich in B cells and CD3+ T cells [ 46 ]. Although TME existed heterogeneity, one study identified the core immune-related genes (IGLL5 and IL2RA) in ccRCC and papillary renal cell carcinoma [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-adjacent renal tissue may have oncological relevance,that the tumor progression or local recurrence may be associated with the molecular status of the tumor adjacent tissue [ 52 , 53 ]. The tumor microenvironment (TME), including immune cells,adjacent normal cells and so on plays a crucial role in influencing tumor behavior and progression [ 54 ]. Some interesting yet complex events occur at tumor borders that contribute to the aberrant molecular changes occurring in adjacent renal tissue.…”
Section: Discussionmentioning
confidence: 99%